PENGARUH OPERATING EXPENSES TO OPERATING REVENUES (BOPO), FINANCING TO DEPOSIT RATIO (FDR) DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Wardannah, Mella Kusuma; Wirman, Wirman (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
The development of Islamic banking is currently growing rapidly and has gained a lot of trust in the community which greatly affects the nation's economy. This study aims to examine the influence of Operating Expenses to Operating Revenues (BOPO), Financing To Deposit Ratio (FDR) and Non-Performing Financing (NPF) on the Profitability of Islamic Commercial Banks in Indonesia in the 2015-2019 period. The data is taken from the annual financial reports of Sharia Commercial Banks registered with the Financial Services Authority in 2015-2019 which are published on the official website (www.ojk.co.id) The object of this research was conducted at 6 banks registered with the Financial Services Authority (OJK) with a period of 5 years for the 2015-2016 period. In total there are 6 Sharia commercial banks, namely Bank Muamalat, Bank Mega Syariah, Bank BRI Syariah, Bank BNI Syariah, Bank BCA Syariah, and Bank Mandiri Syariah. The data analysis technique used in the study used the classical assumption test which included normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. To find out the overall picture of each of the variables, this study uses multiple linear regression and hypothesis testing which includes the t test (partial) and the f test simultaneously. The results showed that the BOPO variable had a significant negative effect on ROA, the FDR variable had a significant positive effect on ROA and the NPF variable had no effect on ROA. The results of this study are expected to be a guideline for further research and be useful for the management of Islamic Commercial Banks in managing the company.Keywords : Operating Expenses To Operating Revenues (BOPO), Financing To Deposit Ratio (FDR), Non Performing Financing (NPF), Profitabilitas (ROA)